Integrer la notion de service ecosystemique dans les politiques et les pratiques agricoles des pays du Sud - Meral, Philippe (2022)
The notion of ecosystem services has become an essential part of institutional and academic discourses, despite controversies and criticisms. Initially promoted by biodiversity conservationists, it has been deployed in agriculture for several years. Although the idea that ecosystem functionalities are a determining factor in agricultural production is not new, this notion allows us to highlight the new challenges linked to climate change and growing food needs. Since these issues are particularly important in the context of the Global South, comprising most of the so-called low-and middle-income countries (LMIC), it is important to consider the relevance of this concept in terms of practices and policies. This article, which introduces the thematic issue of Cahiers Agricultures aA Agriculture and ecosystem services in the Global SouthaA, traces the emergence of this notion and discusses its importance in the context of ecological intensification of agriculture before presenting the articles that make up this thematic issue. While adopting a critical stance towards the notion, particularly when it is backed by payment mechanisms, the paper insists on the need of co-constructing with farmers the frames of reference for action to adopt.